2016
DOI: 10.1002/ijgo.12020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sonographic endometrial patterns and endometrial thickness as predictors of ectopic pregnancy

Abstract: Evaluation of endometrial thickness and pattern by TVS helps to identify women with a pregnancy of unknown location for close supervision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
(67 reference statements)
0
11
1
Order By: Relevance
“…12 Furthermore, the endometrium is significantly thinner in an ectopic pregnancy than in an intrauterine pregnancy. 13 Characteristic fallopian tube rings are often present during early tubal pregnancy. 14 This condition is due to thickening of the fallopian tube wall by edema, and formation of pregnancy tissue and blood clots in the tube cavity together.…”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, the endometrium is significantly thinner in an ectopic pregnancy than in an intrauterine pregnancy. 13 Characteristic fallopian tube rings are often present during early tubal pregnancy. 14 This condition is due to thickening of the fallopian tube wall by edema, and formation of pregnancy tissue and blood clots in the tube cavity together.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Yadav et al 11 suggested that the combination of endometrial stripe thickness and an endometrial sonographic pattern was a sensitive and specific way of predicting pregnancy outcome. They suggested the cut-off point of 9.8 mm for initial endometrial stripe thickness, which differentiated EP from IUP.…”
Section: Discussionmentioning
confidence: 99%
“…This is why some studies have focused on the role of endometrial stripe thickness and sonographic endometrial pattern, as predictors of an outcome with a PUL. 1016…”
Section: Key Takeawaysmentioning
confidence: 99%
“…Observation of endometrial morphology: The echoes of the endometrium was observed. Then, the endometrial patterns were divided into three types based on the Gonen system: type A, trilaminar pattern (endometrial three-layer pattern), consisting of hyperechoic outer and middle layers, hypoechoic inner layers, and evident echo at the intrauterine midline; type B, relatively homogeneous hyperechoic endometrium, with unclear endometrial layers, obscure intrauterine midline echo, but clear interface between endometrial and muscular layers; and type C, homogeneous hyperechoic endometrium without intrauterine midline echo [5] (Fig. 1).…”
Section: Two-dimensional Gray-scale Ultrasound Modementioning
confidence: 99%